Superdesign : Italian radical design 1965-75 - Didero, Maria Cristina (New York : Monacelli Press, 2017)
"SuperDesign' is the only comprehensive look at the short-lived but powerfully influential movement known as Italian Radical design. In numerous exclusive interviews, unreleased photographs, original drawings and artwork unearthed from personal archives, and newly commissioned photography of rarely seen works. What started as a largely student-led rally against the establishment and a rejection of accepted design norms became a movement that brought together some of the most dynamic and avant-garde thinkers and creative makers across the country. Through enigmatic, confrontational, and even distasteful objects and interiors, peppered with subversive performances and astonishingly innovative advertising campaigns, the Radicals projected design's new era as equal parts pop art, surrealism, play, and futurism. Alongside the exclusive primary source material, 'SuperDesign' features additional essays by top design scholars Deyan Sudjic and Catharine Rossi, as well as prominent collector Dennis Freedman. This book demystifies these fantastic works and tells the stories behind the often contentious relationships between the key figures of the movement (some of whom remain at odds still, nearly fifty years later)"--Publisher's description.
boek
Keywords: Italië